Optimal duration of prior endocrine therapy predicts the efficacy of Fulvestrant in a real‐world study for patients with hormone receptor‐positive and HER2‐negative advanced breast cancer - Zhao, Yannan (Cancer Med, 2020)
Fulvestrant 500 mg is standard of care for endocrine therapy‐naive or pretreated women with hormone receptor‐positive (HR+) metastatic breast cancer (MBC). This study was conducted to explore the potential factors and duration of last endocrine therapy as predictors for the efficacy of fulvestrant 500 mg on Chinese patients in real‐world practice. Two hundred and fifty‐two MBC patients who were treated with fulvestrant 500 mg consecutively between January 2011 and December 2015 in our institute were included in this study. Efficacy outcomes included progression‐free survival (PFS), overall survival (OS), and clinical benefit rate (CBR). The optimal cut‐off value for duration of last endocrine therapy was determined by survival ROC analysis. Adverse events were graded according to NCI‐CTC AE 4.0. Fulvestrant 500 mg demonstrated a median PFS of 5.8 months (95%CI 4.6‐6.9), and a median OS of 35.9 months (95%CI 30.2‐41.4). CBR was 41.3% (95%CI 35‐47). Liver metastasis, bone alone metastasis, lines of endocrine therapy for MBC, and sensitivity to last endocrine therapy were statistically significant in the Cox multivariate analysis (P values of 0.022, 0.02, 0.03, and 0.038, respectively). The optimal cut‐off values for duration of last endocrine therapy to predict the efficacy of fulvestrant 500 mg were 25.08 months for adjuvant endocrine therapy and 5.17 months for first‐line endocrine therapy, which showed no difference in prediction power with ABC clinical definition. Patients with prior adjuvant endocrine therapy ≥25.08 months or first‐line therapy≥5.17 months reached a longer PFS of fulvestrant (p = 0.04). Six patients discontinued the treatment due to intolerable adverse events. Patients with the duration of prior endocrine therapy longer than optimal cut‐off points indicate better PFS of fulvestrant. Liver metastasis, bone alone metastasis, line of fulvestrant, and sensitivity to last endocrine therapy were also predictors for response of fulvestrant. ClinicalTrials.gov Identifier: NCT03708432.